A Review of Palm Oil Plasma Land Conflicts from The Perspective of Agrarian Reform: Analysis of Decision Number 3661 K/PDT/2019 - Trifosa, Shalomita; Maulida Hasanah, Nisa; Nurlinda, Ida (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: The government has addressed disparities in palm oil plantation ownership through the partnership model of the Nucleus Estate Smallholder Plantation (PIR-BUN) using a core-plasma scheme as outlined in Presidential Instruction No. 1 of 1986, aiming to achieve agrarian reform. However, in practice, the nucleus-plasma scheme has led to land conflicts and issues, one of which occurred in Teluk Bakung Village, West Kalimantan. Therefore, to ensure the effective implementation of the nucleus-plasma scheme in the future and the realization of agrarian reform, it is necessary to investigate the causes of plasma land conflicts in Teluk Bakung Village and the impacts of these conflicts on agrarian reform efforts. This study adopts a normative juridical method, examining secondary data from literature and primary data from Supreme Court Decision No. 3661 K/PDT/2019 concerning PT PALM’s default in profit-sharing on plasma land. The findings indicate that plasma land conflicts arise from differing interpretations of the 20% provision for community plantation development, inadequacies in institutional support and processes for the PIR-BUN program, and a lack of transparency from the nucleus company. These conflicts ultimately negatively impact the socio-economic aspects of plasma farmers in Teluk Bakung Village and hinder agrarian reform efforts, particularly in the region. Keywords: Agrarian Reform, PIR-BUN, Plasma Land